The Influence of Traditional Games on Freestyle Swimming Speed in Riau Aquatic Pekanbaru Swimming Association Athletes - Rezki Rezki; Sesi Melati; Fezyana Delsa Anugrah; Muhammad Ikhsan (UNIB Press, 2024)
Increased swimming speed can be attributed to factors such as improved motor coordination, physical endurance, and possibly other benefits gained through traditional play. This study aims to evaluate the effect of participation in traditional games on increasing freestyle swimming speed in athletes who are members of the Riau Aquatic Swimming Association in Pekanbaru. This study used an experimental approach by dividing athletes into two groups: a group that underwent additional traditional game sessions and a control group that underwent regular training without additional intervention. Swimming speed measurements were carried out before and after the intervention period. The results of the T test in table 4 for the experimental group obtained a calculated T value = 29.665 > T table = 2.052 and a sig value. (2.tailed) = 0.000 < 0.05. The conclusion of the research shows that traditional games have a significant influence on freestyle swimming speed in athletes from the Riau Aquatic Swimming Association, Pekanbaru, Riau Province.